Penyuluhan Hukum Undang-Undang Informasi dan Transaksi Elektronik di Kabupaten Ogan Ilir - Busroh, Firman Freaddy; Khairo, Fatria; Erleni, Erleni; Zhafirah, Putri Difa; Andini, Riski (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
North Indralaya District is one of the sub-districts in Ogan Ilir Regency which has large potential agricultural areas, especially for horticulture, namely vegetable crops. Horticultural development efforts have recently received more serious attention to support the country's economic development program. If agricultural development is carried out, farmers' knowledge and abilities must increase and change so that the ultimate goal of agricultural development can be achieved, namely improving the welfare of farmers in particular and the people in general. The STIH-Sumpah Pemuda PkM Team will conduct legal counselling on the Information and Electronic Transactions Law in Ogan Ilir Regency regarding understanding the use of technology and information in everyday life through simple animated videos that are easy for the public to understand. Apart from that, this activity also has added value, namely that the community is expected to be able to use digital market platforms to increase the distribution of agricultural products for the people of North Indralaya to meet market needs both nationally and internationally. So it is hoped that there will be an increase in trade in agricultural products from conventional patterns to digital patterns.